Celebrity endorsement and the fashion world an emerging trend: the leverage of celebrity endorsement towards consumer buying behavior - Gomathy A/P Sangara Murthi, . (2011)
This paper responds to the call for greater understanding of celebrity endorsement in fashion world. Term of celebrity is normally associated with individuals who are frequently in the public eye and typically have a high profile in, amongst others, the sport and entertainment industries. The focus of the paper lies in the how much of the Malaysia consumers’ was leveraged by celebrity endorsement in Fashion world. The customer attitude towards celebrity endorsements get products sold out faster than the normal process. The results from a survey conducted on 100 Malaysian respondents provide insight into how consumers’ perceptions are on celebrity endorsers.